Problematika : Guru - Esi Yulianti; Arifin (Jurnal Korpus, 2026)
This research aims to determine teacher problems in learning Indonesian using a genre pedagogy approach at SMPN 7 Bengkulu City. This research uses a qualitative descriptive research method, where the data sources in this research are students and Indonesian language teachers at SMPN 7 Bengkulu City. The research results show that in general, teachers have an understanding of genre pedagogy and its stages, the problem lies in its implementation which is not in accordance with the 4 stages of genre pedagogy. Teachers have not implemented the 4 stages of genre pedagogy. At the stage of building context, reviewing the model, the teacher only carries out discussions and questions and answers, without further discussion activities. The stages of guided construction and independent construction have also not been fully implemented. The teacher's problem in the 4 stages of genre pedagogy is that the teacher already knows the 4 stages of genre pedagogy but it has not been implemented during direct classroom learning, the teacher has not been able to explain it well so that the students become a problem teacher, in reality the students do not understand the teacher's explanation because the teacher has not been able to explain well, which means the teacher has not read the instructions from the teacher's book.